Overexpression of microRNA-722 fine-tunes neutrophilic inflammation by inhibiting Rac2 in zebrafish - Alan Y. Hsu; Decheng Wang; Theodore Gurol; Wenqing Zhou; Xiaoguang Zhu; Hsiu-Yi Lu; Qing Deng (The Company of Biologists, 2017)
Neutrophilic inflammation is essential for defending against invading pathogens, but can also be detrimental in many clinical settings. The hematopoietic-specific small Rho-GTPase Rac2 regulates multiple pathways that are essential for neutrophil activation, including adhesion, migration, degranulation and production of reactive oxygen species. This study tested the hypothesis that partially suppressing rac2 in zebrafish neutrophils by using a microRNA (miRNA) would inhibit neutrophil migration and activation, which would reduce the immunological damage caused by systemic inflammation. We have generated a transgenic zebrafish line that overexpresses microRNA-722 (miR-722) in neutrophils. Neutrophil motility and chemotaxis to tissue injury or infection are significantly reduced in this line. miR-722 downregulates the transcript level of rac2 through binding to seed-matching sequence in the rac2 3'UTR. Furthermore, miR-722-overexpressing larvae display improved outcomes in both sterile and bacterial systemic models, which correlates with a robust upregulation of the anti-inflammatory cytokines in the whole larvae and isolated neutrophils. Finally, an miR-722 mimic protects zebrafish from lethal lipopolysaccharide challenge. Together, these results provide evidence for and the mechanism of an anti-inflammatory miRNA that restrains detrimental systemic inflammation.